A truncation in the RYR1 gene associated with central core lesions in skeletal muscle fibres. Issue 2 (9th February 2007) - Rossi, Daniela; De Smet, Patrick; Lyfenko, Alla; Galli, Lucia; Lorenzini, Stefania; Franci, Daniela; Petrioli, Francesco; Orrico, Alfredo; Angelini, Corrado; Tegazzin, Vincenzo; Dirksen, Robert; Sorrentino, Vincenzo
Abstract : A novel single-nucleotide deletion in exon 100 of the RYR1 gene, corresponding to deletion of nucleotide 14 510 in the human RyR1 mRNA (c14510delA), was identified in a man with malignant hyperthermia and in his two daughters who were normal for malignant hyperthermia. This deletion results in a RyR1 protein lacking the last 202 amino acid residues. All three subjects heterozygotic for the mutated allele presented with a prevalence of type 1 fibres with central cores, although none experienced clinical signs of myopathy. Expression of the truncated protein resulted in non-functional RYR1 calcium release channels. Expression of wild-type and RyR1 R4836fsX4838 proteins resulted in heterozygotic release channels with overall functional properties similar to those of wild-type RyR1 channels. Nevertheless, small differences in sensitivity to calcium and caffeine were observed in heterotetrameric channels, which also presented an altered assembly/stability in sucrose-gradient centrifugation analysis. Altogether, these data suggest that altered RYR1 tetramer assembly/stability coupled with subtle chronic changes in Ca 2+ homoeostasis over the long term may contribute to the development of core lesions and incomplete malignant hyperthermia susceptibility penetrance in individuals carrying this novel RYR1 mutation.